2004
DOI: 10.1007/s00441-003-0843-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced subcommissural organ glycoprotein immunoreactivity precedes aqueduct closure and ventricular dilatation in H-Tx rat hydrocephalus

Abstract: The H-Tx rat has fetal-onset hydrocephalus associated with closure of the cerebral aqueduct and a reduction in the secretory cells of the subcommissural organ (SCO), a circumventricular organ situated in the dorsal wall of the cerebral aqueduct. The objective of this study was to determine the role of the SCO in hydrocephalus pathogenesis. Serial brain sections through aqueduct regions containing the SCO from H-Tx rats, together with non-hydrocephalic Fischer F344 rats, were studied at E16, before hydrocephalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…The initial events in the brain that lead to hydrocephalus are not well understood. Recently, however, it was demonstrated that ventricular dilatation is preceded by underdevelopment of the subcommissural organ (SCO), an ependymal secretory gland in the dorsal cerebral aqueduct, and is associated with a reduction in immunostaining of the secretory glycoprotein (Somera and Jones 2004). This is consistent with other evidence for a link between SCO function and hydrocephalus in that many animal models have an SCO deficiency (Pérez-Fígares et al 2001).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…The initial events in the brain that lead to hydrocephalus are not well understood. Recently, however, it was demonstrated that ventricular dilatation is preceded by underdevelopment of the subcommissural organ (SCO), an ependymal secretory gland in the dorsal cerebral aqueduct, and is associated with a reduction in immunostaining of the secretory glycoprotein (Somera and Jones 2004). This is consistent with other evidence for a link between SCO function and hydrocephalus in that many animal models have an SCO deficiency (Pérez-Fígares et al 2001).…”
Section: Introductionsupporting
confidence: 59%
“…Histological examination of brains-In a previous study it was shown that H-Tx pups with potentially severe hydrocephalus at 0-1 days of age have an abnormal cerebral aqueduct and hypoplasia of the subcommissural organ, whereas H-Tx pups without ventricular dilatation and Fischer F344 pups do not have these features (Somera and Jones 2004). In this study, C10, C11, and C17 congenic rats all appeared to be completely normal when compared to the same region in F344 rats.…”
Section: Characterization Of the Single Congenic Strainssupporting
confidence: 47%
See 2 more Smart Citations
“…In regards to its main function, CSF overproduction by the choroid plexus is a rare a cause of hydrocephalus [3] [8] [241]. [252] and exhibits decreased glycoprotein immunoreactivity [253], and the subfornical organ can become damaged as the condition progresses [254].…”
Section: Choroid Plexusmentioning
confidence: 99%